PENGARUH GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Mukhlizul Hamdi; Putri Ayu; Kasman Karimi (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2022)
This study aims to examine the board of directors, management ownership, independent board of commissioners and company size on company performance. The population of this study are basic and chemical industrial companies listed on the Indonesia Stock Exchange (IDX) with an observation period of 2016 to 2020. The sample in this study used the purposive sampling method, so that only 23 companies from 78 companies could be sampled. The results of the study prove that only managerial ownership and company size have a significant effect on company performance, while independent boards of directors and commissioners have no significant influence on company performance. The implication of this research is to prove that management ownership and firm size have an effect on company performance.